Development of an IoT-Based 3-Phase Electric Motor Controller Trainer Equipped to Improve Critical Thinking Skills, Creativity, and Learning Outcomes: Supporting SDG 4 - Joko Joko; Ismet Basuki; Tri Rijanto; Aries Dwi Indriyanti; Alfredo Arianto Permana Putra (Journal of Current Studies in SDGs, 2026)
Objective: To develop a learning device for an Internet of Things (IoT)-based Right-Left Rotating Induction Motor Control Trainer equipped with Student Worksheets (LKM) to improve critical thinking skills, creativity, and student learning outcomes. Method: The research method used the ADDIE model development research. The testing or evaluation process is carried out a validity test, a student response test, and an effectiveness test. Data analysis techniques using descriptive statistics, N-Gain test, and Paired Samples Test. Results:  The results show that the Internet of Things (IoT)-based Right-Left Rotating Induction Motor Control Trainer equipped with Student Worksheets is highly valid based on expert validation results, highly practical based on student responses, and highly effective in terms of improving critical thinking, creativity, and student learning outcomes. Therefore, the resulting trainer is highly suitable for use in electrical machinery lectures. Novelty: The novelty of this research lies in the integration of an IoT-based Right-Left Rotating Induction Motor Control Trainer with Student Worksheets and learning outcome measurements covering cognitive, affective, and psychomotor domains. This study highlights how technology-based learning innovation supports SDG 4 by promoting quality education, competency development, and improved learning experiences.